2023
DOI: 10.1007/s11060-023-04274-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of Glioma Grade 4: technical update from the neuro-oncology section of the Italian Society of Neurosurgery (SINch®): a systematic review

Abstract: Purpose The extent of resection (EOR) is an independent prognostic factor for overall survival (OS) in adult patients with Glioma Grade 4 (GG4). The aim of the neuro-oncology section of the Italian Society of Neurosurgery (SINch®) was to provide a general overview of the current trends and technical tools to reach this goal. Methods A systematic review was performed. The results were divided and ordered, by an expert team of surgeons, to assess the Class o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 353 publications
0
16
0
Order By: Relevance
“…The association between resection of the MET uptake area and outcomes should be investigated with consideration of MGMT mutations. Postoperative MRI was conducted at a later stage than recommended in the current guidelines (Grabowski et al., 2014 ; Ius et al., 2023 ), which may have hindered our ability to accurately assess the postoperative Gd area (Garcia‐Ruiz et al., 2021 ). On the other hand, the threshold of Gd‐EOR > 70% we used for comparison is typically applied to postoperative MRIs performed at shorter intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between resection of the MET uptake area and outcomes should be investigated with consideration of MGMT mutations. Postoperative MRI was conducted at a later stage than recommended in the current guidelines (Grabowski et al., 2014 ; Ius et al., 2023 ), which may have hindered our ability to accurately assess the postoperative Gd area (Garcia‐Ruiz et al., 2021 ). On the other hand, the threshold of Gd‐EOR > 70% we used for comparison is typically applied to postoperative MRIs performed at shorter intervals.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment has been shown to improve the survival rate (Grabowski et al., 2014 ; Lacroix et al., 2001 ; Lopez‐Rivera et al., 2021 ; Sanai et al., 2011 ). The intraoperative use of 5‐aminolevulinic acid (5‐ALA; Christodoulides & Lavrador, 2021 ), a neuro‐navigation system based on MRI images of the tumor, and awake surgery are common techniques employed to achieve maximum resection while preserving normal functional tissue (Ius et al., 2023 ; Youngblood et al., 2021 ). Recently, the usefulness of fluorescence imaging during GBM surgery has been reported (Cao et al., 2022 ; Li et al., 2018 ; Shen et al., 2021 ; Shi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 Neuro-oncology surgeons in Europe have recently called on clinicians prescribing dexamethasone to glioma patients to be wary of these potential complications and use dexamethasone judiciously. 14 In addition to the aforementioned adverse effects, dexamethasone is also associated with myopathy, altered appetite, poor sleep, mood disturbance, and other effects, including psychosis, mania, depression, anxiety, delirium, and dementia. Studies indicate that these are not rare occurrences, occurring in up to 5% to 10% of patients receiving high-dose steroids.…”
Section: Dexamethasone Use In Perioperativementioning
confidence: 99%
“…In vitro, in vivo, and clinical studies have reported conflicting evidence on glioblastoma cell aggressiveness with dexamethasone, but with some reporting increased glioma stem cell proliferation and angiogenesis 13 . Neuro-oncology surgeons in Europe have recently called on clinicians prescribing dexamethasone to glioma patients to be wary of these potential complications and use dexamethasone judiciously 14 …”
mentioning
confidence: 99%
“…Glioma grade 4 (GG4) tumors, which include astrocytoma IDH-mutant grade 4 and the astrocytoma IDH wt (that currently defines the glioblastoma class) are the most common and aggressive primary tumors of the central nervous system [ 1 3 ]. Compelling evidence, based on objective tumor volume analysis, supports the role of the extent of resection (EOR) in high grade glioma patients as the first step of patients management.…”
Section: Introductionmentioning
confidence: 99%